1996
DOI: 10.1182/blood.v87.3.1179.bloodjournal8731179
|View full text |Cite
|
Sign up to set email alerts
|

Detection of altered membrane phospholipid asymmetry in subpopulations of human red blood cells using fluorescently labeled annexin V

Abstract: The phospholipids of the human red cell are distributed asymmetrically in the bilayer of the red cell membrane. In certain pathologic states, such as sickle cell anemia, phospholipid asymmetry is altered. Although several methods can be used to measure phospholipid organization, small organizational changes have been very difficult to assess. Moreover, these methods fail to identify subpopulations of cells that have lost their normal phospholipid asymmetry. Using fluorescently labeled annexin V in flow cytomet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
150
1
2

Year Published

1997
1997
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 285 publications
(165 citation statements)
references
References 28 publications
10
150
1
2
Order By: Relevance
“…6A; note absence of yellow staining in merged image, fourth column). Finally, the analysis of the apoptotic rate by flow cytometry evaluation of annexin V binding, which depends on phosphatidylserine exposure at the cell surface (32), demonstrated that DMC, at least at the low concentration used in these experiments (0.2 g/ml), was not cytotoxic per se, but did impair GD3 traffic, and did significantly reduce CD95/ Fas-triggered cell death (Fig. 6B).…”
Section: Microtubular Network Integrity Is Required For the Redistribmentioning
confidence: 79%
“…6A; note absence of yellow staining in merged image, fourth column). Finally, the analysis of the apoptotic rate by flow cytometry evaluation of annexin V binding, which depends on phosphatidylserine exposure at the cell surface (32), demonstrated that DMC, at least at the low concentration used in these experiments (0.2 g/ml), was not cytotoxic per se, but did impair GD3 traffic, and did significantly reduce CD95/ Fas-triggered cell death (Fig. 6B).…”
Section: Microtubular Network Integrity Is Required For the Redistribmentioning
confidence: 79%
“…An apparent correlation between an oxidative damage and the loss of PS asymmetry has been reported in RBC from patients with important human diseases, including sickle cell anemia, thalassemia, glucose-6-phosphate dehydrogenase deficiency, and diabetes (32,(36)(37)(38)(39). PS externalization, a well-defined sign of apoptosis, contributes to the shortened life span of defective erythrocytes (36,(40)(41)(42)(43)(44) as well as to important changes occurring in RBC function such as hypercoagulability (45,46). On the other hand, overproduction of reactive oxygen species has been associated with PS asymmetry and has been considered of great importance in determining cell fate, that is, senescence or death (3).…”
Section: Discussionmentioning
confidence: 99%
“…Annexin V binding to RBC. The fraction of annexin V labelled RBC was determined by flow cytometry with slight modifications to those described elsewhere (Koopman et al, 1992;Tait & Gibson, 1994;Kuypers et al, 1996). Citrated whole blood was diluted 1:10 with a HEPES buffer consisting of HEPES-Na 10 mmol/l, NaCl 136 mmol/l, KCl 2 .…”
Section: Methodsmentioning
confidence: 99%